Clinical and Laboratory Findings in Early Diagnosis of Bacterial Meningitis - Emel Ulusoy; Anıl Mert Özçelik; Ali Öztürk; Hale Çitlenbik; Durgül Yılmaz; Murat Duman (Galenos Yayinevi, 2020)
Introduction:Acute bacterial meningitis is an important cause of morbidity and mortality in childhood. Early diagnosis and treatment are vital in emergency departments. The aim of this study was to determine the clinical and laboratory findings that can predict bacterial meningitis in the early period.Methods:Patients between one month and 17 years of age, who underwent lumbar puncture with pre-diagnosis of central nervous system infection in pediatric emergency department between January 2014 and December 2017, were evaluated. Demographic data, admission complaints, physical examination findings, laboratory results, and treatments were reviewed.Results:Four hundred-seventeen children (57.6% male) were included in the study. 119 cases (28.5%) were at the age of 3 months and under, 127 cases (30.5%) were at the age of 3 months-3 years and 171 cases (41%) were older than 3 years. Presence of neurological findings (169 cases, 40.5%), vomiting (118 cases, 28.3%), seizures (86 cases, 20.6%) and headache (76 cases, 18.2%) were frequently identified at presentation. Central nervous system infection was detected in 159 cases (38.1%) [32 cases (7.7%) bacterial meningitis and 127 cases (30.4%) aseptic meningitis]. In clinical complaints, vomiting was found to be significantly higher in both bacterial and aseptic meningitis than in non-meningitis patients. (p<0.001 and p=0.032, respectively), while headache and signs of meningeal irritation were higher in aseptic meningitis than in non-meningitis patients (p<0.001 and p<0.001, respectively). White blood cell count, neutrophil count and C-reactive protein values were found to differentiate bacterial meningitis (p=0.017, p <0.041 and p <0.004, respectively).Conclusion:In this study, vomiting as clinical findings and white blood cell count, neutrophil count and C-reactive protein values were found to be helpful in the differentiation of bacterial meningitis in patients who had lumbar puncture due to central nervous system infection.